Inherited Thrombocytopenia Related Genes: GPS2 Mediates the Interplay Between ANKRD26 and ETV6 - Valeria Capaci; Melania Eva Zanchetta; Giorgia Fontana; Daniele Ammeti; Roberta Bottega; Michela Faleschini; Anna Savoia (Cells)
Mutations in the genes ANKRD26, RUNX1, and ETV6 cause three clinically overlapping thrombocytopenias characterized by a predisposition to hematological neoplasms. The ANKRD26 gene, which encodes a protein involved in protein-protein interactions, is downregulated by RUNX1 during megakaryopoiesis. Mutations in 5′UTR of ANKRD26, leading to ANKRD26-RT, disrupt this regulation, resulting in the persistent expression of ANKRD26, which leads to impaired platelet biogenesis and an increased risk of leukemia. Although ANKRD26 and ETV6 exhibit inverse expression during megakaryopoiesis, ETV6 does not regulate the ANKRD26 expression. Hypothesizing an interplay between ETV6 and ANKRD26 through in vitro studies, we explored the interactions between the two proteins. In this study, we found that ANKRD26 interacts with ETV6 and retains it in the cytoplasm, phenocopying ETV6-RT-related mutants. We found that GPS2, a component of the NCoR complex, binds both ANKRD26 and ETV6, mediating this interaction. Furthermore, ANKRD26 overexpression deregulates ETV6 transcriptional repression, supporting a common pathogenic mechanism underlying ANKRD26-RT, FPD/AML, and ETV6-RT. Our results unveil a novel ANKRD26-ETV6-GPS2 axis, providing new insights to investigate the molecular mechanism underlying thrombocytopenias with a predisposition to myeloid neoplasms that need to be further characterized.